PENGARUH KETERAMPILAN MENGAJAR GURU DAN KESIAPAN BELAJAR SISWA TERHADAP HASIL BELAJAR PADA MATA PELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN (PKK) KELAS XI BDP NEGERI 1 PEMATANGSIANTAR - Rudy Fransiskus Nainggolan; Herlina Hotmadinar Sianipar; Anton Luvi Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to find out whether there is an influence on teachers' teaching skills and students' learning readiness on the PKK Class XI BDP SMK Negeri 1 Pematangsiantar academic year 2024/2025. The variables in this research are teachers' teaching skills and students' learning readiness as independent variables and learning outcomes as dependent variables. This type of research is quantitative descriptive research, with a population of all class Data collection techniques were carried out by observation and distributing questionnaires, while data analysis techniques used validity tests, reliability tests, normality tests, multiple linear regression tests, t tests, f tests and coefficient of determination tests.Based on the results of data analysis, it was found that there was a significant influence between the teacher's teaching skills on the learning outcomes of class Then, there is a significant influence between learning readiness on student learning outcomes, this result can be seen from the value ????ℎ???????????????????? 2.19 > ???????????????????????? 1.985, and it is concluded that Ho is rejected and Ha is accepted, meaning that the teacher's teaching skills and learning readiness variables have an influence on the results studying class XI BDP students at SMK Negeri 1 Pematangsiantar. Then there is a joint or simultaneous influence between the teacher's teaching skills and learning readiness on learning outcomes, seen from the value ????ℎ???????????????????? (5.86) > value ???????????????????????? (3.09). The R Square coefficient of determination test shows that the influence of teacher teaching skills on student learning outcomes is 44.1% and the remaining 55.9% is influenced by other factors and the influence of learning readiness on student learning outcomes is 48.4% and the remaining 51.6% influenced by other factors.